Nurses Providing End-of-Life Care for Infants and Their Families in the NICU: A Review of the Literature. (December 2018) - Gibson, Kim; Hofmeyer, Anne; Warland, Jane
Abstract : Background: Nurses working in the neonatal intensive care unit (NICU) who care for dying infants and their families say they do not necessarily have the expertise or the specific training to provide quality end-of-life-care (EOLC). Purpose: The purpose of this review was to critically appraise the existing qualitative literature regarding nurses' experiences when caring for infants during end of life in the NICU and to identify barriers and enablers to provide quality EOLC. Search Strategy: A literature search was conducted using CINAHL and OVID databases. Studies that explored nurses' experiences when caring for infants who were dying or when lifesaving care was withdrawn were retrieved and 15 studies were thematically analyzed. Results: Five major themes emerged: advocating for the dying infant, building close relationships with the family, providing an appropriate care environment, nurses' emotional responses to dying or death, and professional inadequacy in EOLC. Implications for Practice: Nurses face multiple challenges when providing EOLC including moral dilemmas and feelings of professional inadequacy. Avoidance was a common strategy used by nurses to cope with the stress associated with EOLC. Managers can foster quality EOLC by implementing education sessions about infant mortality, EOLC, advocacy, team communication, and self-care practices. Implications for Research: Research could evaluate the effectiveness of EOLC education sessions to build nurses' competence and confidence in advocacy and EOLC clinical skills.